PROTECTIVE ACTIVITY OF THE STEM BARK AQUEOUS EXTRACT OF MUSANGA CECROPIOIDES IN CARBON TETRACHLORIDE- AND ACETAMINOPHEN-INDUCED ACUTE HEPATOTOXICITY IN RATS - Adeneye, A. A. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
The hepatoprotective activities and the mechanisms of actions of Musanga cecropioides stem bark aqueous extract (MCW) were investigated on acute hepatocellular injuries induced by intraperitoneal (IP) carbon tetrachloride (CCl4) (20% CCl4/olive oil, 1.5 mL/kg) and 800 mg/kg/IP of acetaminophen (APAP) in normal saline, in male Wistar rats. Among the Yorubas (South-West Nigeria), cold decoction of MCW is used as a natural antidote for oral gastric poisonings, infective hepatitis and other liver diseases. Its hepatoprotective activities were monitored by assaying for the serum aminotransferases, ornithine carbamoyl transferase and the toxicant-induced histopathological lesions in rat livers 24 hours post-induction. These enzymes are markers of acute hepatic injuries and their elevations are indications of acute liver injuries. Pretreatment of rats with graded doses (125 - 500 mg/kg) of MCW significantly attenuated the acute elevation of the liver enzymes and the hepatotoxin-induced histopathological lesions in the rat livers. The presence of two active natural antioxidants (flavonoids and alkaloids) in high concentrations in MCW may account for the hepatoprotective activities observed in this study. These results, thus, support the folkloric use of MCW for treatment of hepatic injuries resulting from acute gastric poisonings, infective hepatitis or other liver diseases.